Family Resilience Among Family Members of Intensive Care Unit Patients: A Qualitative Meta‐Synthesis - Zhouyan Zhai; Wenjing Wu; Ling Wei; Huiyuan Xue; Shan Zhang; Jiaqi Chen; Xia Yin (Nursing in Critical Care, 2026)
ABSTRACT Background ICU critical illness places heavy psychological and financial burdens on families, weakening their coping capacity. Although family resilience helps mitigate these issues, systematic research on experiences and processes of family resilience operating in ICU family members is still lacking. Aims To systematically review and synthesize the existing qualitative evidence on the experiences and operational processes of family resilience among family members of ICU patients and provide suggestions for the development of interventions in future studies. Study Design The qualitative meta‐synthesis was conducted in accordance with The Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ). We searched eight major databases, including PubMed, CINAHL, Web of Science, Embase, CNKI, Wanfang Database, VIP Database and Sinomed from their inception to January 2026. The studies' quality was evaluated using the Joanna Briggs Institute (JBI) Critical Appraisal Tool for Qualitative Research (2020 version) by two reviewers independently. Thematic synthesis was used to integrate and analyse the findings. Findings Eight eligible studies (11 papers) were screened out from 613 retrieved records. Quality assessment classified one study as Level A and all others as Level B across the included literature. Common methodological limitations involved incomplete reporting of researcher‐reflexivity accounts, researcher‐participant relational dynamics and formal ethics approval documentation. The meta‐synthesis identified the following five core themes: (1) Dynamic Multidimensional Family Adversities from Critical Illness, (2) Dynamic Adaptation and Restructuring of Family Functioning Patterns, (3) Proactive acquisition and integration of multi‐level external support resources, (4) Construction of individual and internal family belief systems and (5) Dual Impacts of ICU Crises on Families. Conclusions Family resilience relies on internal and external resources. Positive cognition and proactive behaviours promote family growth and resource utilization, helping families cope with multiple stressors during ICU hospitalization. Relevance to Clinical Practice These findings guide ICU medical and nursing staff to assess family resources and mental status, design targeted interventions and strengthen family resilience.